Kearifan Lokal Minangkabau sebagai Sumber Belajar Matematika dalam Pendidikan Dasar - Masniladevi , (Prosiding Seminar Nasional Jurusan PGSD FIP UNP Tahun 2015, 2015)
PMRI importance of implementation in an effort to achieve the goal of learning mathematics in elementary school run should be, but the reality is very different when the researchers looked at the lecture in the classroom, many teachers or prospective teachers who have difficulties in learning design using a context that is around the students. Cultivating local knowledge as a source of learning in basic education became one of the alternatives in realizing the role of basic education and to build the nation's independence in this era of modernization. Local wisdom instilled early on became a strong foundation to continue to maintain local wisdom itself. All forms of local wisdom can be used as a learning resource in the implementation of learning in the classroom. Teachers also do not design learning that trains students to find a formula of waking up the space. Though many contexts that can be used, for example, carving patterns on the fabric songket, the longhouse, and a dance area. It is study referencies; this study will produce a learning device geometry for elementary school students in the city of Padang. Until now, there has been no design mathematics in elementary geometry are valid on the material in SD. Teachers have not been able to associate the idea of ​​mathematical thinking in the cultural context of use as props geometry. Whereas the application of the concept of geometry in SD indispensable understood by students